2016
DOI: 10.1007/s11916-016-0568-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Headache Therapy in the Athlete

Abstract: Post-traumatic headache can occur after any traumatic brain injury, regardless of severity. Headache is consistently the most common symptom following concussion and occurs in over 90% of athletes with sports-related concussion. Despite this prevalence, the complaint of headache after a possible concussive injury is often dismissed. Even when sports-related concussion is accurately diagnosed, many athletes fall victim to mismanagement of this associated symptom by clinicians who are not well-versed in headache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 61 publications
0
15
0
2
Order By: Relevance
“…The most common symptoms observed clinically following a single mTBI include cognitive deficits in the acute stage, typically resolving within months of the initial injury [ 65 ]. Given the prevalence of post-concussive symptoms such as headache persisting for weeks to months following a single injury, the data presented within this study and others suggest that a single mTBI is enough to cause long term pathological changes within the brain [ 66 ]. Animal models have demonstrated that a single mTBI can acutely induce neurodegenerative and neuroinflammatory changes that increase with injury severity, and that this is intensified with repeated trauma [ 67 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms observed clinically following a single mTBI include cognitive deficits in the acute stage, typically resolving within months of the initial injury [ 65 ]. Given the prevalence of post-concussive symptoms such as headache persisting for weeks to months following a single injury, the data presented within this study and others suggest that a single mTBI is enough to cause long term pathological changes within the brain [ 66 ]. Animal models have demonstrated that a single mTBI can acutely induce neurodegenerative and neuroinflammatory changes that increase with injury severity, and that this is intensified with repeated trauma [ 67 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Headache is the most common symptom in concussed patients [ 1 ]. Migraine headache, tension headache, cervico-genic headache and post-traumatic headache are all observed in the concussed-patient population [ 31 , 32 , 33 ]. Red flags for the patient with post traumatic headache include a deteriorating level of consciousness, progressive worsening, vomiting, early morning headache and headache worsening in the supine position.…”
Section: H Is For Headachesmentioning
confidence: 99%
“…In a recent case-control observational study, Eckner showed an association between migraine headaches and concussion, concluding that pre-existing migraine headaches are a risk factor for chronic headache reporting after concussion [ 31 ]. Seifert cautioned that headaches could represent an exacerbation of pre-concussion headaches, rather than a new brain injury [ 32 ]. The treatment of post-traumatic migraine or post-traumatic tension headaches was considered important.…”
Section: H Is For Headachesmentioning
confidence: 99%
“…Clinical manifestations in the domains of the oculomotor system, affective disturbances, vestibular signs, cardiovascular anomalies, subtypes of headache and somatization are not prompted by the SCAT-5. All these difficulties have been documented in concussed patients, can affect prognosis, and be meritorious of treatment [ 6 , 9 , 10 , 11 , 21 , 23 , 24 , 25 , 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Red flags must always be reviewed with concussion for significant intra-cranial pathology, however, once this has been ruled out, treatment of headache can be based on the specific type of headache documented. The most common headaches associated with concussion have been migraine, tension, post-traumatic and cervicogenic [ 20 , 21 ]. Pre-existing migraines have been associated with poorer outcomes post-concussion.…”
Section: Introductionmentioning
confidence: 99%